The Effect of Scaffolding-Based Problem-Based Learning on Creative Thinking Skills on Hormone Materials - M. Dwi Wiwik Ernawati*; Sudarmin Sudarmin; Asrial Asrial; Haryanto Haryanto (Jurnal Pendidikan Sains Indonesia, 2023)
The ability to think creatively is one of the higher order thinking skills so it is very important in biochemistry learning. The purpose of this study was to determine students' interest in learning in problem-based learning by providing scaffolding and without providing scaffolding and to see the effect of students' interest in learning in problem-based learning by providing scaffolding on  students' creative thinking abilities. The design in this study used an explanatory sequential design with a total sample of 88 students of the Jambi University chemistry education study program. The instrument used in this study was a learning interest questionnaire with 17 statements and a creative thinking ability test question with a total of 10 questions. The data collection procedure was carried out, namely the researcher distributed a questionnaire instrument of student learning interest when learning using the PBL model and learning using the scaffolding integrated PBL model. After distributing the interest in learning questionnaire, the researcher then distributed the instruments for testing the ability to think creatively. The sampling technique used was total sampling. The data analysis technique used descriptive test, t-test and simple linear regression test. The results obtained are that there are differences in students' interest in learning when learning using the PBL model integrated with scaffolding and learning using the PBL model. In addition, there is an influence of students' interest in learning on students' creative thinking skills using a problem-based learning model with scaffolding